Enhancing toxin-based vaccines against botulism. Issue 6 (1st February 2018) - Przedpelski, Amanda; Tepp, William H.; Zuverink, Madison; Johnson, Eric A.; Pellet, Sabine; Barbieri, Joseph T.
Highlights: In a mouse model of botulism, M-BoNT/A1 was not toxic at >10 6 -fold greater amounts than native BoNT/A. M-BoNT/A1(W1266A) (M-BoNT/A1 W ) was created to prevent neuronal cell binding. M-BoNT/A1 vaccination protected against challenge by 10 6 LD50 of native BoNT/A1. LCHCN elicited a higher neutralizing antibody titer than HCC, showing neutralizing epitopes within LCHCN . Engineered BoNT with defects in catalysis and receptor binding is a novel vaccine strategy against botulism. Abstract: Botulinum neurotoxins (BoNT) are the most toxic proteins for humans. BoNTs are single chain proteins with an N-terminal light chain (LC) and a C-terminal heavy chain (HC). HC comprises a translocation domain (HCN ) and a receptor binding domain (HCC ). Currently, there are no approved vaccines against botulism. This study tests a recombinant, full-length BoNT/A1 versus LCHCN /A1 and HCC /A1 as vaccine candidates against botulism. Recombinant, full-length BoNT/A1 was detoxified by engineering 3-amino acid mutations (E224A/R363A/Y366F) (M-BoNT/A1) into the LC to eliminate catalytic activity, which reduced toxicity in a mouse model of botulism by >10 6 -fold relative to native BoNT/A1. As a second step to improve vaccine safety, an additional mutation (W1266A) was engineered in the ganglioside binding pocket, resulting in reduced receptor binding, to produce M-BoNT/A1 W . M-BoNT/A1 W vaccination protected against challenge by 10 6 LD50 Units of native BoNT/A1, while M-BoNT/A1 or M-BoNT/A1 W vaccination equally protected against challenge by native BoNT/A2, a BoNT subtype. Mice vaccinated with M-BoNT/A1 W surviving BoNT challenge had dominant antibody responses to the LCHCN domain, but varied antibody responses to HCC . Sera from mice vaccinated with M-BoNT/A1 W also neutralized BoNT/A1 action on cultured neuronal cells. The cell- and mouse-based assays measured different BoNT-neutralizing antibodies, where M-BoNT/A1 W elicited a strong neutralizing response in both assays. Overall, M-BoNT/A1 W, with defects in multiple toxin functions, elicits a potent immune response to BoNT/A challenge as a vaccine strategy against botulism and other toxin-mediated diseases.